2021
DOI: 10.7759/cureus.15803
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Induced Left Sciatic Neuropathy Requiring Prolonged Physical Medicine and Rehabilitation

Abstract: A growing number of case reports and series have described a wide spectrum of neurological manifestations of COVID-19 disease including encephalopathy, cerebrovascular disease, and Guillain-Barre syndrome (GBS). However, peripheral neuropathy associated with COVID-19 disease has been uncommonly reported.Here, we describe a young patient with a COVID-19 infection who developed unilateral sciatic neuropathy during the course of treatment requiring prolonged physical medicine and rehabilitation stay. She was trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…There is a case of painful neuropathy associated with the COVID-19, which is an uncommon type of a neuropathy 4 . A case of sciatic neuropathy was reported by Acharya et al with some similarities to the case we have reported 5 .…”
Section: Covid-19 Associated Unilateral Sciatic Neuropathysupporting
confidence: 85%
“…There is a case of painful neuropathy associated with the COVID-19, which is an uncommon type of a neuropathy 4 . A case of sciatic neuropathy was reported by Acharya et al with some similarities to the case we have reported 5 .…”
Section: Covid-19 Associated Unilateral Sciatic Neuropathysupporting
confidence: 85%
“…The results were compiled and presented descriptively in Table 1 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) .…”
Section: Resultsmentioning
confidence: 99%
“…Mononeuritis was identified in five patients admitted to the intensive care unit, either brachial or peroneal mononeuritis. There are a few reports in the literature, and they are attributed to vasculitis-like mechanisms of the vasa nervorum ( 43 ). Four patients had polyneuropathy, but because of logistic limitations during the pandemic, we were not able to assess between Guillain-Barre syndrome and other types of neuropathies, such as critical illness polyneuropathy.…”
Section: Discussionmentioning
confidence: 99%